Hubungan Media Sosial dan Pengetahuan Remaja Putri dengan Seks Pranikah dalam Pencegahan Pernikahan Dini - Nurhilsa, Siti; Haryanti, Dwi; Mariana, Silvia; Ningsih, Nisa Kartika (Jurnal Akademika Baiturrahim Jambi, 2025)
Early marriage is a marriage carried out by a couple who is still underage. The negative impacts that can result from early marriage include stunting, maternal and infant mortality rates, health problems, high school dropout rates, and poverty. According to data from the Central Statistics Agency in 2019, Jambi Province is in 7th position in terms of marriage rates before the age of 18 (14.8%). The aim of this research is to determine the relationship between social media and young women’s knowledge about premarital sex in preventing early marriage. This research is observational and cross sectional. The research location is at the Ummahatul Mukminin Islamic Boarding School in Sungai Bertam, Jambi. The population was 60 people, using total sampling. Some respondents use social media highly, as many as 42 people (70%) and most respondents have sufficient knowledge, as many as 24 people (40%). There is a significant relationship between social media and young women’s knowledge about premarital sex in preventing early marriage with a p-value of 0.021 and 0.001. It is hoped that the results of this research can be used as material for consideration by health workers in contributing to improving the quality of maternal and child health services, especially in midwifery services within the adolescent scope. Education about premarital sex in schools is routinely carried out to increase knowledge and provide a negative picture of premarital sexual behavior.